Intramolecular Proton and Charge Transfer of Pyrene‐based trans‐Stilbene Salicylic Acids Applied to Detection of Aggregated Proteins. Issue 22 (8th October 2018) - Zhang, Jun; Wang, Jun; Sandberg, Alexander; Wu, Xiongyu; Nyström, Sofie; LeVine, Harry; Konradsson, Peter; Hammarström, Per; Durbeej, Bo; Lindgren, Mikael
Abstract: Two analogues to the fluorescent amyloid probe 2, 5‐bis(4′‐hydroxy‐3′‐carboxy‐styryl)benzene (X‐34) were synthesized based on the trans ‐stilbene pyrene scaffold (Py1SA and Py2SA). The compounds show strikingly different emission spectra when bound to preformed Aβ1–42 fibrils. This remarkable emission difference is retained when bound to amyloid fibrils of four distinct proteins, suggesting a common binding configuration for each molecule. Density functional theory calculations show that Py1SA is twisted, while Py2SA is more planar. Still, an analysis of the highest occupied molecular orbitals (HOMOs) and lowest unoccupied molecular orbitals (LUMOs) of the two compounds indicates that the degree of electronic coupling between the pyrene and salicylic acid (SA) moieties is larger in Py1SA than in Py2SA. Excited state intramolecular proton transfer (ESIPT) coupled‐charge transfer (ICT) was observed for the anionic form in polar solvents. We conclude that ICT properties of trans ‐stilbene derivatives can be utilized for amyloid probe design with large changes in emission spectra and decay times from analogous chemical structures depending on the detailed physical nature of the binding site. Abstract : New probes ! Two new amyloid probes based on the trans ‐stilbene pyrene scaffold (Py1SA and Py2SA), showing strikingly different emission spectra when bound to amyloid fibrils are reported.